2016
DOI: 10.1016/j.pss.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Properties of interstellar dust responsible for extinction laws with unusually low total-to-selective extinction ratios of R=1−2

Abstract: It is well known that the extinction properties along lines of sight to Type Ia supernovae (SNe Ia) are described by steep extinction curves with unusually low total-to-selective extinction ratios of R V = 1.0-2.0. In order to reveal the properties of interstellar dust that causes such peculiar extinction laws, we perform the fitting calculations to the measured extinction curves by applying a two-component dust model composed of graphite and silicate. As for the size distribution of grains, we consider two fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Another possible interpretation is that the low RV values are caused by dust in the interstellar (IS) medium. This would require IS clouds in the SN host galaxies to be characterized by smaller dust grains compared to those seen in our Galaxy (Gao et al 2015;Nozawa 2016), possibly as a consequence of cloud-cloud collisions induced by the SN radiation pressure (Hoang 2017). Evidences supporting the IS scenario were given by Phillips et al (2013) who found a strong correlation between the extinction of SNe Ia and the strength of a diffuse interstellar band at 5870Å.…”
Section: Introductionmentioning
confidence: 78%
“…Another possible interpretation is that the low RV values are caused by dust in the interstellar (IS) medium. This would require IS clouds in the SN host galaxies to be characterized by smaller dust grains compared to those seen in our Galaxy (Gao et al 2015;Nozawa 2016), possibly as a consequence of cloud-cloud collisions induced by the SN radiation pressure (Hoang 2017). Evidences supporting the IS scenario were given by Phillips et al (2013) who found a strong correlation between the extinction of SNe Ia and the strength of a diffuse interstellar band at 5870Å.…”
Section: Introductionmentioning
confidence: 78%
“…polarization (λ max < 0.4 µm) for several SNe Ia 9,10 . Numerical modeling of dust extinction 11 and polarization curves 12 toward individual SNe Ia demonstrate that the anomalous values of R V and λ max can be reproduced by the enhancement in the relative abundance of small grains to large grains in the host galaxy.…”
Section: Introductionmentioning
confidence: 93%
“…Another possibility for this dispersion is grain growth. The ratio of total-to-selective extinction, R V , is generally correlated with grain size (Nozawa 2016;Cardelli et al 1988). Estimates of R V for the low-extinction line-of-sight sample (Table 1) are found using spectral classifications (Wright et al 2003) and optical and NIR photometry (Høg et al 2000;Skrutskie et al 2006).…”
Section: Dispersion In λ Max (A V )mentioning
confidence: 99%